Teaching Children to Programming on the Example of the Scratch Program (Eurasian Scientific Herald, 2022)
This article is devoted to teaching children programming using the Scratch program as an example. Like a human, a computer communicates in its own language. It is a computer-only language that has limited vocabulary and strict spelling rules. A "language" that a computer understands and communicates with is called a programming language. Anyone who knows any programming language can easily create their own program